Big COVID, Red State: The Value of Over-Communication in a Public Health Crisis - Schneider, Jen (Frontiers in Communication, 2021)
This Community Case Study examines the challenges of communicating about the COVID-19 crisis in a politically conservative American state, Idaho. The study presents an analysis of one local expert’s communication strategies in the face of significant partisanship, threats of violence, and widespread refusal to comply with recommended public health behaviors. Findings suggest that consistent, cross-platform communication that emphasizes personalized recommendations and advice, transparency, and humility, are key strategies in a fractured information environment. However, while micro-level communication strategies are important, more must be done to help Americans regain trust in institutions, expertise, and information at a macro-level.